Modelling the wave climate at the Port of East London to understand the complex hydrology affecting sedimentation - Matiwane, Lukhanyo Lesedi (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMil)--Stellenbosch University, 2025.